La incomunicabilidad en el debate medieval: Ricardo de San Víctor, Tomás de Aquino y Duns Escoto - Lourenco, Santiago Dias (Sapientia, 2023)
The paper aims to outline a historical line from the Greco-Roman definition of person to the notion of incommunicability (incomunicabilitas existentia). Within the context of medieval Latin thought, Richard of St. Victor, Thomas Aquinas, and Duns Scotus developed an alternative approach to the definition of person, proposed by Boethius, focused on the concept of substance.